The Moral Significance of Death in Georg Simmel’s Metaphysics of Life - Staiti, Andrea (Simmel Studies, 2017)
In this paper I discuss the significance of Simmel’s conception of death as presented in his capstone work Lebensanschauung (1918). I argue for Simmel death is the form of all cultural forms and that it has a transcendental, form-giving function for life in its concrete unfolding. I conclude with a brief examination of the thought of immortality and some suggestions about how Simmel’s conception of death has a bearing on current issues such as the increment of life-expectancy in developed countries.